Reconstruction of Corporate Legal Arrangements in Indonesia Relating to Corporate Social and Environmental Responsibility in the Mining Sector - Riyadi, Padlah (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Rule of article 74 UUPT has regulation of CSR of Voluntary becomes mandatory. Philosophically that arrangement is based on article 33 paragraphs (3) and (4) of the 1945 Constitution, while from its empirical fact it does not stop from environmental impact and damage which is generated by activity mining of itself. From the results of research also showing that the rule of regulation related to mining area itself contains the principle of CSR.